Hydrogen production mechanism and catalytic productivity of Ni-X@g-C3N4 (X = precious and non-precious promoter metals) catalysts from KBH4 hydrolysis under stress loading and atmospheric pressure: Experimental analysis and molecular dynamics approach - Celik, Fatih Ahmet; Aygun, Murat; Karabulut, Ezman; Onat, Erhan; Izgi, Mehmet Sait; Yilmaz, Muecahit; Ayguen, Zeynep (Elsevier Science Sa, 2024)
In this study, the pressure effect of Ni-based catalysts added a second promoter metal to increase of catalyst performance supported a graphite carbon nitride (g-C3N4) monolayer on hydrogen release mechanisms from potassium boron hydride (KBH4) hydrolysis was investigated using molecular dynamics (MD) method based on tight-binding density functional theory (DFT). The use of the various promoters, such as transition metals (X = Cu, Ta and W) and noble metals (X = Pd, Pt and Rh) with applying a high external pressure was investigated to understand the role on catalytic performance of the Ni-based catalysts under stress loading. The g-C3N4 monolayer doped with Ni-X nano-catalysts was used for efficient H-2 release from KBH4 hydrolysis. The computational results show that the number of H-2 shows more increment with MD time for NiW and NiRh catalysts than other NiTa and NiCu (transition metals) and NiPd and NiPt (noble metals) under 0 GPa pressure. On the other hand, a notable increase in H-2 amount is seen only NiCu and NiRh catalysts under 50 GPa. Also, the mechanism of the H-2 production reaction from KBH4 hydrolysis of g-C3N4 doped NiCo catalysts was clarified. High-performance cost metal catalysts such as NiCo was investigated as both experimentally and modeling under atmospheric pressure to enhance its commercial application value. Some experimental applications and analyzes were also performed to measure the accuracy of the modeling for the relevant molecular groups in the system.
Keywords: Nickel-based catalyst; Promoter role; Potassium borohydride; Molecular dynamics; DFT; G-C2N4